2018
DOI: 10.1016/j.coph.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy as a cytoprotective mechanism in esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is amongst the most aggressive human malignancies, representing a significant health burden worldwide. Autophagy is an evolutionarily conserved catabolic process that degrades and recycles damaged organelles and misfolded proteins to maintain cellular homeostasis. Alterations in autophagy are associated with cancer pathogenesis, including ESCC; however, the functional role of autophagy in ESCC remains elusive. Here, we discuss the clinical relevance of autophagy effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…On the other hand, constitutive autophagy is often associated with tumor progression and poor survival outcomes in human cancers, including pancreatic cancer, 111 colorectal cancer (CRC), 112 gliomas, 113 and esophageal cancer. 114 Cancer cells are strongly adaptive in response to environmental insults, and thus the metabolic alterations characteristic to autophagy contribute to a phenomenon called “austerity,” or a tolerance to nutrient deprivation. 43,112 Tumors that exhibit resistance to uneven perfusion and poor nutritive blood flow in the tumor environment, like pancreatic tumors, benefit from autophagy-mediated upkeep of metabolites, whereas reversal of austerity can be achieved via artificial repression of autophagy, leading to resensitivity to starvation and subsequent cell death 43 .…”
Section: The Two Faces Of Autophagymentioning
confidence: 99%
“…On the other hand, constitutive autophagy is often associated with tumor progression and poor survival outcomes in human cancers, including pancreatic cancer, 111 colorectal cancer (CRC), 112 gliomas, 113 and esophageal cancer. 114 Cancer cells are strongly adaptive in response to environmental insults, and thus the metabolic alterations characteristic to autophagy contribute to a phenomenon called “austerity,” or a tolerance to nutrient deprivation. 43,112 Tumors that exhibit resistance to uneven perfusion and poor nutritive blood flow in the tumor environment, like pancreatic tumors, benefit from autophagy-mediated upkeep of metabolites, whereas reversal of austerity can be achieved via artificial repression of autophagy, leading to resensitivity to starvation and subsequent cell death 43 .…”
Section: The Two Faces Of Autophagymentioning
confidence: 99%
“…It degrades and removes damaged organelle components in cells to maintain the homeostasis of cells and provides nutritional support for cell survival [5]. Previous studies have found that abnormal autophagy is associated with a variety of human diseases such as Alzheimer's disease, cardiovascular disease, and several types of cancer including ESCC [6][7][8]. As the first autophagy-specific gene identified, Beclin-1 plays an important role in the regulation of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…In the early stage of ESCA, autophagy can activate anti-tumor cells and micro-environment to inhibit the development of ESCA [16]. However, in the middle and later stages of ESCA, autophagy can be used as a promoter of tumor development, by clearing abnormal mitochondria and providing energy for tumor cells, and then promote the proliferation and metastasis of tumor cells [17]. Whelan et al have also demonstrated that autophagy can promote the metastasis of ESCA by mediating the mechanism of epithelial-mesenchymal transition (EMT) [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cancer can change the normal autophagy mechanism, and autophagy-related gene mutations can lead to the occurrence of cancer [5].…”
Section: Introductionmentioning
confidence: 99%